The Concept of Experimental Psychology as Part of the Reconstruction of Islamic Psychology: An Educational Perspective - Rahman, Imas Kania; Andriana, Nesia; Elita, Desi (LPPM Universitas Negeri Jakarta, 2024)
This study explores the integration of experimental psychology within an Islamic framework to contribute to the reconstruction of Islamic psychology from an educational perspective. Using qualitative descriptive analysis, this research examines how experimental methods, when adapted to Islamic ethical standards, can enhance the validation and applicability of Islamic psychological concepts in educational settings. Findings indicate that while experimental psychology offers valuable tools for empirical inquiry, its application within Islamic psychology requires modifications that respect spiritual dimensions central to Islam. This integration supports a holistic approach to student development, addressing cognitive, emotional, and moral growth. The study highlights the potential for a culturally relevant educational model that aligns with both scientific rigor and Islamic values, offering a foundation for further research and practical applications in Islamic educational psychology